MHC class I genes in the owl monkey: Mosaic organisation, convergence and loci diversity (2005)
The MHC class I molecule plays an important role in immune response, pathogen recognition and response against vaccines and self- versus non-self-recognition. Studying MHC class I characteristics thus became a priority when dealing with Aotus to ensure its use as an animal model for biomedical research. Isolation, cloning and sequencing of exons 1–8 from 27 MHC class I alleles obtained from 13 individuals classified as belonging to three owl monkey species (A. nancymaae, A. nigriceps and A. vociferans) were carried out to establish similarities between Aotus MHC class I genes and those expressed by other New and Old World primates. Six Aotus MHC class I sequence groups (Ao-g1, Ao-g2, Ao-g3, Ao-g4, Ao-g5 and Ao-g6) weakly related to non-classical Catarrhini MHC were identified. An allelic lineage was also identified in one A. nancymaae and two A. vociferans monkeys, exhibiting a high degree of conservation, negative selection along the molecule and premature termination of the open reading frame at exon 5 (Ao-g5). These sequences’ high conservation suggests that they more likely correspond to a soluble form of Aotus MHC class I molecules than to a new group of processed pseudogenes. Another group, named Ao-g6, exhibited a strong relationship with Catarrhini’s classical MHC-B-C loci. Sequence evolution and variability analysis indicated that Aotus MHC class I molecules experience inter-locus gene conversion phenomena, contributing towards their high variability